Smart Mobility and Elderly People. Can ICT Make the City More Accessible for Everybody? - Battarra, Rosaria; Zucaro, Floriana; Tremiterra, Maria Rosa (TeMA - Journal of Land Use, Mobility and Environment, 2018)
The ageing population is a phenomenon whose relevance grows over time and quickly spreads in different territorial contexts. Therefore, cities will have to take into account the ageing population and define policies and strategies to improve the quality of life. For this purpose is particularly remarkable the transport sector because it allows to use the urban services and to promote an active ageing. Within the field of urban studies aimed at facing the new challenges related to social developments, including that of the ageing population, the Smart City paradigm has been spread to make cities safe, accessible and sustainable. The strategies to improve accessibility and safety of the mobility system using ICTs can have positive impacts in terms of ensuring elderly people the ability to lead an autonomous life and participate actively in society according to one’s individual needs. In this framework, the aim of the paper is to analyse how Italian cities are declining the topic of Smart Mobility, with particular attention to the use of new technologies to improve the elderly trips. The paper attempt to show that in the sample of Italian cities analysed the ICTs applied to the transport sector do not fully realize their potential; this is not due to the limited fields of application, but rather to the lack of a “system-orientated” perspective when applying innovations. The adoption of a smart approach cannot be limited to a market-induced uncritical introduction of devices or sensors, instead, it will be necessary to refine the tools for understanding the needs of specific categories of users, such as the elderly, to define integrated strategies able to operate on many aspects simultaneously.